Hiperealitas Relasi Interpersonal Atasan Bawahan Dalam Serial Drama Korea a Businness Proposal - Hotlando Manullang; Delliana Santi (UNIVERSITAS KALBIS, 2026)
Now a days, communication and information technology have touched every aspect of our lives, enabling faster processes and overcoming spatial and temporal constraints. Gone are the days of handwritten letters sent through postal services. It is undeniable that the advancements in information and communication technology have provided us with broader and more accurate sources of information. We now live in an information society, where every facet of our existence is influenced by technology. The rapid development of information and communication technology has ushered the world into the era of globalization. Notably, this globalized world is significantly shaped by media technology. Through global media platforms, human interactions are open and extensive. Furthermore, these media channels play a crucial role in disseminating cultures globally. Easy access to information and communication has made people more aware of diverse cultures. However, cultural exchange doesn’t solely occur through traditional media. Social media platforms, films, and global television series also contribute to the distribution of cultural knowledge across borders.